TRENDS IN THE DEVELOPMENT OF THE TOURISM INDUSTRY IN RUSSIA - Inna V. Butenko (Статистика и экономика, 2016)
This article presents a study of the Russian regions by the number of existing tourist firms and the size of average per capita money income; the analysis of the dynamics of tourist firms and per capita income; the interrelation between the two studied parameters.